Acute Myocardial Infarction Reduces Respiration in Rat Cardiac Fibers, despite Adipose Tissue Mesenchymal Stromal Cell Transplant - Camila I. Irion; Eduarda L. Martins; Michelle L. A. Christie; Cherley B. V. de Andrade; Alan C. N. de Moraes; Raphaela P. Ferreira; Cibele F. Pimentel; Grazielle D. Suhett; Antonio Carlos C. de Carvalho; Rafael S. Lindoso; Adalberto Vieyra; Antonio Galina; et al. (Stem Cells International)
Adipose-derived mesenchymal stromal cell (AD-MSC) administration improves cardiac function after acute myocardial infarction (AMI). Although the mechanisms underlying this effect remain to be elucidated, the reversal of the mitochondrial dysfunction may be associated with AMI recovery. Here, we analyzed the alterations in the respiratory capacity of cardiomyocytes in the infarcted zone (IZ) and the border zone (BZ) and evaluated if mitochondrial function improved in cardiomyocytes after AD-MSC transplantation. Female rats were subjected to AMI by permanent left anterior descending coronary (LAD) ligation and were then treated with AD-MSCs or PBS in the border zone (BZ). Cardiac fibers were analyzed 24 hours (necrotic phase) and 8 days (fibrotic phase) after AMI for mitochondrial respiration, citrate synthase (CS) activity, F0F1-ATPase activity, and transmission electron microscopy (TEM). High-resolution respirometry of permeabilized cardiac fibers showed that AMI reduced numerous mitochondrial respiration parameters in cardiac tissue, including phosphorylating and nonphosphorylating conditions, respiration coupled to ATP synthesis, and maximal respiratory capacity. CS decreased in IZ and BZ at the necrotic phase, whereas it recovered in BZ and continued to drop in IZ over time when compared to Sham. Exogenous cytochrome c doubled respiration at the necrotic phase in IZ. F0F1-ATPase activity decreased in the BZ and, to more extent, in IZ in both phases. Transmission electron microscopy showed disorganized mitochondrial cristae structure, which was more accentuated in IZ but also important in BZ. All these alterations in mitochondrial respiration were still present in the group treated with AD-MSC. In conclusion, AMI led to mitochondrial dysfunction with oxidative phosphorylation disorders, and AD-MSC improved CS temporarily but was not able to avoid alterations in mitochondria function over time.